Tangshen Formula Attenuates Diabetic Kidney Injury by Imparting Anti-pyroptotic Effects via the TXNIP-NLRP3-GSDMD Axis - Li, Nan; Zhao, Tingting; Cao, Yongtong; Zhang, Haojun; Peng, Liang; Wang, Yan; Zhou, Xuefeng; Wang, Qian; Li, Jialin; Yan, Meihua; Dong, Xi; Zhao, Hailing; et al. (Frontiers in Pharmacology, 2021)
We previously reported that Tangshen formula (TSF), a Chinese herbal medicine for diabetic kidney disease (DKD) therapy, imparts renal protective effects. However, the underlying mechanisms of these effects remain unclear. Pyroptosis is a form of programmed cell death that can be triggered by the NLRP3 inflammasome. Recently, the association between the pyroptosis of renal resident cells and DKD was established, but with limited evidence. This study aimed to investigate whether the renal protective effects of TSF are related to its anti-pyroptotic effect. DKD rats established by right uninephrectomy plus a single intraperitoneal injection of STZ and HK-2 cells stimulated by AGEs were used. In vivo, TSF reduced the 24 h urine protein (24 h UP) of DKD rats and alleviated renal pathological changes. Meanwhile, the increased expression of pyroptotic executor (GSDMD) and NLRP3 inflammasome pathway molecules (NLRP3, caspase-1, and IL-1β) located in the tubules of DKD rats were downregulated with TSF treatment. In vitro, we confirmed the existence of pyroptosis in AGE-stimulated HK-2 cells and the activation of the NLRP3 inflammasome. TSF reduced pyroptosis and NLRP3 inflammasome activation in a dosage-dependent manner. Then, we used nigericin to determine that TSF imparts anti-pyroptotic effects by inhibiting the NLRP3 inflammasome. Finally, we found that TSF reduces reactive oxygen species (ROS) production and thioredoxin-interacting protein (TXNIP) expression in AGE-stimulated HK-2 cells. More importantly, TSF decreased the colocalization of TXNIP and NLRP3, indicating that ROS-TXNIP may be the target of TSF. In summary, the anti-pyroptotic effect via the TXNIP-NLRP3-GSDMD axis may be an important mechanism of TSF for DKD therapy.